Implementasi Pendekatan Contextual Teaching and Learning Untuk Meningkatkan Keaktifan dan Hasil Belajar Pendidikan Pancasila Kelas II SD - Putri, Annisa; Hindun, Iin; Suharni, Sri (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to improve student engagement and learning outcomes through the implementation of the Contextual Teaching and Learning (CTL) approach using the Environmental Awareness Train Exploration method in the Pancasila Education subject, particularly on the topic of Environmental Awareness. The research employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, which includes planning, action, observation, and reflection stages across two cycles. The participants were 23 second-grade students of Class 2A at SDN Tunjungsekar 1, Malang City. Instruments used in the study included student engagement observation sheets, participation questionnaires, as well as pre-test and post-test assessments. The results showed that the implementation of the Contextual Teaching and Learning approach through the Environmental Awareness Train Exploration effectively enhanced student engagement and learning outcomes significantly and sustainably. Student engagement increased from 67% in the pre-cycle, which falls into the Fair category, to 86% in Cycle I and 96% in Cycle II, both of which fall into the Very Good category. In terms of learning outcomes, the average pre-test score of 73 improved to 87 in Cycle I and reached 94 in Cycle II, with an N-Gain score of 0.78, categorized as high. These results indicate that the Contextual Teaching and Learning approach is effective in improving both student engagement and learning outcomes among elementary students. Thus, the implementation of the Contextual Teaching and Learning can serve as an alternative for teachers or future researchers to enhance student engagement and learning outcomes in other learning topics.